RADT-12. USE OF FDOPA PET FOR RADIATION THERAPY TARGETING IN GRADE 2 IDH MUTANT GLIOMA. (12th November 2021) - Cordova, James; Mazur, Thomas; Mitchell, Timothy; Perez-Carrillo, Gloria; Wang, Qing; Wang, Yong; Ponisio, Maria; Huang, Jiayi
Abstract: BACKGROUND: Low-grade, IDH mutant (IDHmt) gliomas typically do not enhance on MRI complicating radiotherapy (RT) target delineation. Amino acid PET using 3, 4-dihydroxy-6-[18F]-fluoro-L-phenylalanine (FDOPA) has demonstrated avidity in IDHmt gliomas and may assist in RT planning for non-enhancing tumors. This study aims to compare conventional and FDOPA-defined target volumes in grade 2 IDHmt gliomas. METHODS: In a prospective pilot study, patients underwent MRI and FDOPA PET using a 3T MRI/PET system followed by standard therapy. Gross tumor volumes (GTV) included the T2/FLAIR abnormality and surgical cavity; clinical target volumes (CTV) included a 1 cm expansion constrained anatomically. Metabolic target volumes (MTVs) were generated using the FDOPA SUV > 1.5-fold normal brain isocurve. Union of GTV and MTV generated a fusion GTV (fGTV); expanding fGTV by 1 cm yielded the fusion CTV (fCTV). Target volumes were compared volumetrically with overlap (Dice coefficient) and surface metrics (Hausdorff distance). Medians are reported with ranges. RESULTS: Four patients with grade 2 IDHmt glioma (3 1p/19q codeleted oligodendrogliomas, 1 non-codeleted astrocytoma) received MRI/PET before treatment. All oligodendrogliomas exhibited FDOPA avidity; the astrocytoma showed no avidity. GTV and CTV measured 16.1 cc (4.9 - 82.2 cc) and 76.7 cc (29.5 - 256.1 cc), respectively. The MTV volume outside of GTV was 0.8 cc (0.2 – 6.1 cc), but was covered in each case by the CTV. Addition of FDOPA increased fGTV and fCTV volumes by 5.4% and 17.5%, respectively. Dice coefficient and Hausdorff distances for GTV vs fGTV were 0.96 (0.95 - 0.99) and 11.2 mm (10.0 – 11.9 mm), respectively, and for CTV vs fCTV were 0.87 (0.81 – 0.95) and 10.2 mm (10.0 - 11.0), respectively. CONCLUSIONS: FDOPA PET identified tracer-avid regions outside of MRI-defined GTVs in a group of IDHmt gliomas. FDOPA PET provides useful metabolic information for RT planning and warrants further investigation.